ANALISIS BREAK EVEN POINT SEBAGAI ALAT PERENCANAAN LABA PADA PD RAHMAT MA - Rumiasih, N.A; -, Yudiana; Pratiwi Sakinah, Sarita Dian (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
A company runs its own business merely to obtain and to gain an advantage and profit. The profits amount obtained is presumed as an indicator of both success and failure of company through its management performance. Therefore, It is essential for the management to have their profit planned anually. Applying break-even point analysis tools is one of the way taken in planning the profit. Determining the magnitude of break-even point applied and profit planning achieved by PD Rahmat MA in 2017 and 2018 was the aim of this study. The data used is based on sales, fixed costs and variable costs in 2017 and 2018. The results taken through this research shows that the costs spent each year increase as production and income increase as well. The performance of the company has considerably optimized in order to improve sales to be over the break-even point. Profit planned is 20%, yet surprisingly the company has somehow exceeded the target of expected profit.